A devida informação sobre planejamento sucessório extrajudicial - (:unkn) unknown (Universidade Federal do Pampa, 2024)
Analysis and suggestions to understand a set of projections made in life, to be fulfilled as a manifestation of a special desire, after death. Delimitations in which they present similar legal foundations in a preventive nature, thus avoiding possible conflicts in judicial hereditary successions. Dealing with succession in life represents a great social taboo, a bad omen, which makes the topic somewhat indigestible, commonly postponed to the infinite of the existence of the person who, unfortunately, does not have this non-lasting time available. To a large extent, this is a need to postpone as long as possible, within the limits of inheritance legislation, the distribution and destination of private assets take their due course. Therefore, the lack of information generates discomfort and entrenches prejudice that removes any incentive to learn about extrajudicial ways of approaching patrimonial succession. In this way, the following question will be addressed: What is succession planning and how can we enhance it through the use of legal donation and will tools? The primary objective of this work is to analyze the concept of succession planning, with a special focus on the application of donation and will techniques, and to examine the practical implications associated with each of these strategies. In more specific terms, we initially aim to address the meaning of succession planning, the legal instruments used by this institute, their definitions, requirements and relevant categories, in addition to exploring the benefits and limitations arising from the practical implementation of these measures. The preventive forms that will be addressed are methods that do not require judicial intervention, in ways that are entirely carried out in extrajudicial services, in a way that facilitates the transfer of assets to their heirs or beneficiaries, in an efficient and quick manne
Adequate information about succession planning extrajudicial
Keywords: Planejamento sucessório; Testamento; Doação; Succession planning; Testament; Donation; CNPQ::CIENCIAS SOCIAIS APLICADAS